2018 Power Systems Computation Conference (PSCC) 2018
DOI: 10.23919/pscc.2018.8442756
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced, Risk-Based System Development Process: A Case Study from the Belgian Transmission Network

Abstract: Abstract-A large share of renewable generation raises some unique challenges and is forcing change in the operation and planning of electricity transmission systems. In this paper, using real transmission network data representing a part of the Belgian network, the need for building a large set of credible future operating conditions to identify and validate system development decisions is demonstrated. The paper argues that the traditional approach of checking system development options on a few selected oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Ref. [8] also found that for the case considered there, the critical operating states were to a greater extent characterized by high wind power generation than by high (i.e. peak) system load.…”
Section: Clustering and Identification Of Operating Statesmentioning
confidence: 89%
See 3 more Smart Citations
“…Ref. [8] also found that for the case considered there, the critical operating states were to a greater extent characterized by high wind power generation than by high (i.e. peak) system load.…”
Section: Clustering and Identification Of Operating Statesmentioning
confidence: 89%
“…agglomerate clustering or K-means clustering) was not equally important to obtain accurate estimates for the reliability indices. More recently, several applications of clustering of operating states have been reported for transmission system planning [6]- [8]. Ref.…”
Section: Clustering and Identification Of Operating Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between scenarios as exogenous visions of the future and scenarios as different realisations of local variables, shown here for the example of investment in generation capacity from(Bukhsh, Bell, Vergnol, Weynants, & Sprooten, 2018).…”
mentioning
confidence: 99%